Money Laundering Risk in Batam's Special Economic Zone: Industrial Vulnerabilities and Enforcement Gaps - Ramlan; Darwis Anatami; Parameshwara; Khairul Riza (RADJA PUBLIKA, 2025)
Purpose: This study analyzes the forms of money-laundering risk emerging from industrial activity in the Batam Special Economic Zone (SEZ), evaluates the effectiveness of legal enforcement and preventive measures, and identifies the institutional obstacles that constrain risk mitigation in the zone. Methodology: The research applies a normative-empirical (socio-legal) approach combining statutory and case analysis. Primary data were collected through in-depth interviews with law enforcement officials, financial-intelligence analysts from Indonesia's Financial Transaction Reports and Analysis Center (PPATK), industrial actors, and Batam SEZ authorities, supplemented by secondary data from statutes, court records, and institutional risk assessments, and analyzed using a qualitative-descriptive method. Findings: The Batam SEZ is highly vulnerable to money laundering, particularly through fictitious export-import transactions, under-invoicing, abusive transfer pricing, and the use of shell companies. Although a comprehensive regulatory framework and reporting infrastructure exist, enforcement remains weakened by institutional fragmentation, the absence of fully risk-based supervision, and limited corporate compliance with Anti-Money Laundering standards, patterns that recur across documented cases and parallel compliance failures elsewhere in the zone's regulatory architecture. Limitations: The study is constrained by limited access to confidential financial data and by its focus on a single SEZ; broader comparative research across other zones and jurisdictions is needed. Contribution: The study contributes to the discourse on economic-crime prevention by mapping practical vulnerabilities within SEZ industrial sectors and proposing integrated, risk-based enforcement and asset-recovery strategies, including expanded reporting obligations, strengthened Non-Conviction Based Asset Forfeiture, and the prospective use of Deferred Prosecution Agreements.